Arylsulfatase A pseudodeficiency incidence in Turkey - Emre, Serap; Topçu, Meral; Terzioğlu, Mügen; Renda, Yavuz (The Turkish Journal of Pediatrics, 2000)
Pseudodeficiency (Pd) in arylsulfatase A (ASA) is a relatively frequent condition in healthy individuals. It produces a reduction in enzyme activity similar to that found in metachromatic leukodystrophy (MLD). A variable incidence of the Pd allele was found in different populations; it was 10-20 times higher than that of metachromatic leukodystrophy. Twelve of the 52 unrelated, healthy individuals were found to be heterozygous for the ASA Pd allele. In Turkey we estimated the incidence of the Pd allele as 11.5 percent. Out of 18 cases with MLD, one patient was found homozygous for the Pd allele and the other patient was found heterozygous. Turk J Pediatr 2000; 42: 115-116.